Food Environment Mapping in Urban Informal (Nairobi) and Rural (Makueni) Kenya: A Cross-Sectional Vendor Survey Data (2023) - Odongo, Nicanor Obiero; Akingbemisilu, Tosin Harold; Jordan, Irmgard; Induli, Irene Mudiovo; Termote, Celine (2025)
This dataset originates from a cross-sectional study conducted in 2023 to assess and characterize the food environment in both urban informal and rural settings in Kenya. The primary objective was to map and analyse food availability across vendor locations, with a specific focus on understanding the differences and similarities in food diversity between Nairobi’s Viwandani informal settlement and Makueni’s Kiima Kiu ward. The study aimed to answer key questions, including: i. What types of food vendors operate in urban, informal, and rural settings? ii. What is the diversity of foods available at individual vendor outlets? iii. What is the quality of food environment in terms of healthy and unhealthy food availability? iv. How does food diversity vary within the vendor neighbourhood? v. Are there structural or spatial disparities in vendor distribution and food accessibility across urban and rural settings? The dataset includes geocoded vendor data, vendor typologies (ambulant/mobile vendors, butchers, cereal shops, cooked food street vendors, kiosks, supermarkets, mom-and-pop shops, stalls/tabletop and restaurants, direct farm sales, home vendors and wholesalers. ), food groups sold, and gender of vendors. It also captures vendor neighbourhood food diversity, which offers a novel lens for evaluating the food environment beyond individual vendors. Data were collected using a digital survey tool on Open Data Kit (ODK) and securely managed via the FormShare platform. The study contributes to food systems research by offering scalable methodologies to assess the built food environment, especially in under-researched rural contexts. Major subject areas include food systems, nutrition environment mapping, rural-urban disparities, public health, informal economies, and geospatial analysis. This dataset is particularly useful for researchers, policymakers, and development practitioners interested in food environment profiling, urbanization impacts on food systems, spatial analysis of vendor access, and nutrition-sensitive planning.